Genetic transformation of antisense ACC oxidase in Carica papaya L. cv. Sekaki via particle bombardment - Che Radziah, C.M.Z.; Nurul Shahnadz, A.H.; Naziratul Ain, A.N.; Zainal, Z. (Penerbit Universiti Kebangsaan Malaysia, 2011)
Papaya (Carica papaya L.) is a very important crop in many tropical countries. Climacteric fruits such as papaya are usually harvested once they have reached maturity, which then undergoes rapid ripening during transit and storage. Hence, papaya is highly susceptible to physiological disorders, mechanical damage and fruit over ripening that can cause postharvest losses of papaya production. Therefore, this study was conducted on genetic transformation of antisense ACC oxidase and its effects on papaya fruit ripening. Through anti-sense technology, down regulation of the ACC oxidase gene results in the suppression of ethylene production, thereby delaying fruit ripening that can produce papaya with better quality. Embryogenic callus of Sekaki papaya were bombarded with the pCAMBIA 1301 that contains the antisense ACC oxidase gene driven and flanked by constitutively CaMV35S promoter and NOS terminator also hygromycin (hpt) resistance gene as selectable marker. Helium gas pressure (1350 psi), 1.0 μm gold particle size and two types of parameters manipulated in the bombardment condition were, the number of bombardment (single or double) and the target position (3 cm, 6 cm and 9 cm). Results showed that double bombardment per sample and 6 cm of target position gave the highest percentage of callus survival which is 88% after 4 weeks in a selection medium containing 50mg/l hygromycin. The PCR analysis for antisense ACC oxidase, hpt and Nad5 genes done on the extracted callus genome gave positive results. The remaining bombarded explants are being maintained to obtain viable regenerates for further analyses.